Kinerja Keuangan Perbankan Syariah Sebelum dan Setelah Merger 3 Bank Umum Syariah - Prasetyo Ramadhan; Shierly Margareth Mantiri; Septiana Rahayu; Dohan; Vicaya Citta Dhammo (Jurnal Buana Akuntansi, 2022)
At the end of 2020, the Government of Indonesia through the Minister of State-Owned Enterprises announced that three state-owned Islamic banks, BNI Syariah, BRI Syariah and Bank Syariah Mandiri, will merge into Bank Syariah Indonesia. The merger comes amid the COVID-19 pandemic. The merger process of the three Islamic banks was marked by an agreement contained in the merger certificate. In 2021, on February 1, three Sharia banks BNI Syariah (BNIS), BRI Syariah (BRIS), Bank Syariah Mandiri (BSM) officially became Bank Syariah Indonesia (BSI). The merger of three state-owned Islamic commercial banks has answered the long wait to establish the largest Islamic commercial bank with strong capital. This study aims to analyze the differences in the financial performance of Islamic banking before and after the merger of 3 Islamic commercial banks. This study used secondary data by collecting data from Islamic Banking Statistics published by the Financial Services Authority. This study used Paired Sample T-test as a data analysis method. The results of this study show that there are significant differences in the financial performance of Islamic banks before and after the mergerof 3 Islamic commercial banks. This is because when a company merges, its wealth is automatically accumulated and funding costs are more efficient.